2015
DOI: 10.1089/end.2015.0202
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Lower Urinary Tract Storage Symptoms: Does Prostate Enucleation Differ from Prostate Vaporization for Treatment of Symptomatic Benign Prostatic Hyperplasia?

Abstract: Storage urinary symptoms significantly improved more after HoLEP compared with PVP, irrespective of the generation of GreenLight laser used. Recovery from bothersome storage urinary symptoms after prostate vaporization is time dependent, and baseline degree of storage symptoms, prolonged operative time, and lower percent of postoperative PSA level reduction negatively predicts postoperative improvement of storage symptoms regardless of the laser procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Several studies have shown improvements in storage symptoms after transurethral surgery for bladder outlet obstruction. [27][28][29][30] As was seen in the current study, storage symptoms often take slightly longer to improve compared with voiding symptoms, likely as a result of neuromuscular changes that must take place in the detrusor muscle once the obstruction is removed.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies have shown improvements in storage symptoms after transurethral surgery for bladder outlet obstruction. [27][28][29][30] As was seen in the current study, storage symptoms often take slightly longer to improve compared with voiding symptoms, likely as a result of neuromuscular changes that must take place in the detrusor muscle once the obstruction is removed.…”
Section: Discussionsupporting
confidence: 55%
“…Meanwhile, storage symptoms are also troubling for patients with BPH. The recovery of detrusor function after a surgical procedure for clinical BPH may be influenced by the degree of de-obstruction [22] . TURP is often not extended down to the fibre of the capsule for fear of capsular perforation and severe venous bleeding, therefore amass of adenoma tissues remains after TURP, usually leading to a high postoperative recurrence rate [9] .…”
Section: Discussionmentioning
confidence: 99%
“…has proved that storage urinary symptoms significantly improved more after retrograde enucleation of the prostate compared with prostate vaporization and baseline degree of storage symptoms, prolonged operative time, and lower percent of postoperative PSA level reduction negatively predicts postoperative improvement of storage symptoms. 18 However, storage urinary symptoms also cannot be resolved by retrograde enucleation of the prostate. Therefore, it was critically important to perform the preoperative UDS detection for BPO, which can confirm the operative indication and judged the prognosis of bladder function, especially for the storage function of the bladder.…”
Section: Discussionmentioning
confidence: 99%